Cognition and will. The problem of interpretation in Law and Literature studies from the Claude Romano and Jean-Luc Marion’s phenomenological perspective - Roggero, Jorge Luis (2023)
This article has a double purpose. In the first place, it aims to account for the contribution of Law and Literature studies regarding the problem of interpretation, based on the debate between Ronald Dworkin and Stanley Fish on the relationship between cognition and will. Secondly, the text also intends to introduce Claude Romano and Jean-Luc Marion’s evential phenomenological perspective as a complementary adjustment of Fish’s proposal.